(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The process of primary education is aimed at forming children’s ability to think logically, mental development, worldview, communicative literacy and self-awareness potential, to be physically healthy, to be able to feel the beauty of material existence, to be able to enjoy beauty and elegance, to be able to feel national traditions. and teaches to respect and obey them